ANALISIS KEBUTUHAN PENGEMBANGAN BAHAN AJAR MENULIS CERITA FANTASI PADA KURIKULUM MERDEKA BELAJAR - Laila Masrura; Rustam; Irma Suryani (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
The teacher has an important role in learning activities, one of which is evaluating learning activities. The purpose of this research is to analyze the needs of teachers in developing teaching materials for writing fantasy stories. This study uses a development research model that refers to the Thiagaragan 4D model with limitations in the first stage or the definition stage and the moted used is a descriptive qualitative method. The source of the research data was a junior high school Indonesian teacher in Jambi. Data collection techniques by distributing online questionnaires, interviews, and online FGDs were then analyzed using qualitative data analysis techniques. Based on the results of the needs analysis research on fantasy story material in the independent curriculum, it is less attractive, so material development is needed so that it can form students' writing competence by prioritizing local wisdom. This research is expected to be an evaluation material for teachers to develop teaching materials that are contextual with the conditions of students. Keywords: fantasy story text, Jambi folklore, Free Learning Curriculum